The roles of immune factors in neurodevelopment - Wang, Chong; He, Tingting; Qin, Jie; Jiao, Jianwei; Ji, Fen (Frontiers in Cellular Neuroscience, 2025)
The development of the nervous system is a highly complex process orchestrated by a multitude of factors, including various immune elements. These immune components play a dual role, not only regulating the immune response but also actively influencing brain development under both physiological and pathological conditions. The brain’s immune barrier includes microglia in the brain parenchyma, which act as resident macrophages, astrocytes that support neuronal function and contribute to the inflammatory response, as well as circulating immune cells that reside at the brain’s borders, including the choroid plexus, meninges, and perivascular spaces. Cytokines—soluble signaling molecules released by immune cells—play a crucial role in mediating communication between immune cells and the developing nervous system. Cytokines regulate processes such as neurogenesis, synaptic pruning, and inflammation, helping to shape the neural environment. Dysregulation of these immune cells, astrocytes, or cytokine signaling can lead to alterations in neurodevelopment, potentially contributing to neurodevelopmental abnormalities. This article reviews the central role of microglia, astrocytes, cytokines, and other immune factors in neurodevelopment, and explores how neuroinflammation can lead to the onset of neurodevelopmental disorders, shedding new light on their pathogenesis.